The Legal Analysis of Quranic Revision for Menstruating Women - Alza Nabiel Zamzami Alza; Wahid Hakim Azzaky; Masrur Masrur; Lutfiyah Lutfiyah (The Future of Education Journal, 2024)
There are various differing opinions regarding the legality of Quranic revision for women who are menstruating. This article aims to provide a more comprehensive and in-depth understanding, as well as to bridge the differing views among scholars concerning Quranic revision for menstruating women. This research uses a qualitative method through a library research approach. The data analysis process is carried out in three stages: data condensation, data presentation, and conclusion drawing. This article concludes that the issue of Quranic revision for menstruating women is complex, with various perspectives among scholars. Most scholars agree that menstruating women are not allowed to read the Quran, but there are exceptions permitted to maintain memorization. This opinion is based on the necessity of preserving the memorized Quran, as losing memorization can negatively impact the memorizer, especially for women who are menstruating. Some scholars, such as Sheikh Ali Jum’ah and Imam Malik, allow exceptions under certain circumstances, while other views are stricter. Therefore, it is important for Quran memorizers to understand this ruling so they can adjust their practices in the appropriate context.